Digital Marketing Implementation: Preparing Grace Trans Strategy on Tiktok App - Mathew Timotius; Dika Djatnika (Jurnal Impresi Indonesia, 2024)
Grace Trans, a unit of PT Matari Jelajah Indonesia, is a leading transportation and tour and travel company in Indonesia. The company focuses on providing excellent transportation services for children and adults, including corporate transportation, shuttle buses, and tour buses. Despite its success, Grace Trans faces challenges in international marketing due to limited manpower and lack of optimal social media marketing strategies, such as TikTok. To address this, the researcher analyzed the social media landscape through STP and Thematic Analysis, focusing on content and content pillars to effectively promote tourism in Indonesia through social media marketing. The researcher aims to increase its contribution to the international economy and promote Indonesian culture. By using social media platforms such as TikTok, Grace Trans can leverage its strengths and reach a wider audience, ultimately contributing to the country's economic growth and development.